Isolation and Properties of the Abnormal Factor IX Molecule of Hemophilia BM - Østerud, B.; Lavine, K.; Kasper, C. K.; Rapaport, S. I. (Thrombosis and Haemostasis, 1977)
Abnormal factor IX from a hemophilia Bm patient (F. IX-Bm) has been isolated to homogeneity on SDS Polyacrylamide gel electrophoresis by the same technique utilized for purifying normal F. IX. F. IX-Bm generated no measurable procoagulant activity when incubated with F. XIa in a two-stage F. IXa assay (normal F. IX, 55 sec; F. IX-Bm, >30 min).F. IX-Bm inhibited the activation of F. X by F. VII and ox brain thromboplastin as measured in an amidolytic assay for factor Xa. Normal F. IX also inhibited this reaction but to a five times lesser degree. F. IX-Bm has the same molecular weight on SDS gel electrophoresis as normal F. IX (55,000) and does not differ from normal F. IX in its amino acid composition. F. XIa cleaves F. IX-Bm in the presence of Ca ions at the same rate as it cleaves normal F. IX, yielding a heavy chain of 27,000 molecular weight and a light chain of 16,000 molecular weight. However, the cleavage does not give rise to procoagulant activity. Like normal F. IXa, the cleaved forms of F. IX-Bm appear to bind phospholipid since F. IX-Bm protein was precipitated with phospholipid in the presence of Ca ions. These data support an hypothesis that the abnormality in the F. IX-Bm molecule stems from a defect at the active site.